Psoas Abscess Accompanied by Neonatal Appendicitis: A Case Report - Mehmet Yücel; Fatma Hilal Yılmaz; Nuriye Tarakçı; Nazlı Dilay Gültekin; Hüseyin Altunhan; Hacı Hasan Esen (Galenos Publishing House, 2019)
Neonatal appendicitis is a very rare event leading to acute abdomen manifestation in neonatal period, and is associated with high mortality rates. In these patients, symptoms and findings are not apparent, most of the time, urgent surgery is carried out without preoperative diagnosis; and diagnoses are made with intraoperative or pathological results. In the present case, an neonatal appendicitis case that had psoas abscess with swelling and circulatory disorder in the right leg on the 15th day of life was presented.